2009
DOI: 10.1038/ajg.2009.3
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antibiotic Prophylaxis Reduces Spontaneous Bacterial Peritonitis Occurrence and Improves Short-Term Survival in Cirrhosis: A Meta-Analysis

Abstract: Antibiotic prophylaxis improved short-term survival in treated patients when compared with untreated control groups and reduced the overall risk of infections, including SBP, during follow-up. In summary, antibiotic prophylaxis should be considered for high-risk cirrhotic patients with ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 23 publications
0
51
0
3
Order By: Relevance
“…However, four trials also included patients with prior SBP132 139 142 143 and the remaining have recently been summarised in two meta-analyses 136 137. Surprisingly, these came to different conclusions, most likely due to erroneous data extraction 144.…”
Section: Prevention Of Sbpmentioning
confidence: 99%
“…However, four trials also included patients with prior SBP132 139 142 143 and the remaining have recently been summarised in two meta-analyses 136 137. Surprisingly, these came to different conclusions, most likely due to erroneous data extraction 144.…”
Section: Prevention Of Sbpmentioning
confidence: 99%
“…Criteria for defining advanced liver disease included Child-Pugh scores > 9, bilirubin levels > 2.5 mg/dL, and impaired renal function. The analysis showed that prophylaxis improved short-term survival and reduced the incidence of infections, including SBP [73] . These results suggest that primary prophylaxis has a great impact in the clinical course of patients with low ascites protein content and advanced cirrhosis, and may reduce the incidence of SBP and improve survival.…”
Section: Primary Prophylaxis In Patients With Ascitesmentioning
confidence: 99%
“…A bakteriális transzlokációból származó szóródás elméletét támogatta, hogy amennyiben egyéb úton (például portalis nyomást csökkentő kezelés révén) sikerül a BT mértékét csökkenteni, úgy az SBP incidenciája is csökken [22]. A bél antibiotikummal történt dekontaminációja szintén csökkenti az SBP kialakulásának valószínűségét [23]. Ezek alapján az SBP-t a BT tükrének tartották.…”
Section: áBraunclassified